THE DOMESTICATION OF WOMEN'S ROLES AS A REFLECTION OF ANCIENT PATRIARCHAL TRADITIONS: A REFLECTION ON THE THOUGHTS OF FRIEDRICH ENGELS AND FATIMAH MERNISSI - Yahya Yahya Abdullah; Roibin Roibin; Ahmad Qiram As-Suvi; Zahrah Salsabillah Ashari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Patriarchal culture and the domestication of women's roles are still significant issues in the Indonesian context. This article reflects the thoughts of Friedrich Engels and Fatimah Mernissi regarding this issue. Friedrich Engels stated that in a patriarchal society, women are often suppressed and marginalized in all aspects of life, including in terms of work and politics, and this, according to Engels, cannot be separated from the values and norms of the past. Meanwhile, Fatimah Mernissi pointed out that patriarchal culture and the domestication of women's roles occur not only in Western society but also in Muslim societies, including Indonesia. Unlike what Engels said, Mernissi underlined that the true spirit of Islam is the spirit of elevating women. In this article, the authors reflect on Engeks and Mernissi's approach in highlighting the origins of the domestication of women's roles and how the historicity of patriarchal culture and the domestication of women's roles have affected the lives of Indonesian women, both in terms of work, politics and family life. Through the reflections of Friedrich Engels and Fatimah Mernissi, this article provides a deeper understanding of issues of patriarchal culture and the domestication of the role of women through the first origins of human civilization and also in the Indonesian context. The author hopes that this article can contribute to efforts to overcome the marginalization of women and create a more just and equitable society for all Indonesian citizens, especially women